Prevalence of the thioamide {⋯H-N-C=S}2 synthon - solid-state (X-ray crystallography), solution (NMR) and gas-phase (theoretical) structures of O-methyl-N-aryl-thiocarbamides - Soo, Y.H. (2014)
10.1039/b514254g